RANCANGAN PENUGASAN OPERATOR PADA AREA KERJA LINTAS PERAKITAN AKHIR PESAWAT NC212I DI PT. DIRGANTARA INDONESIA - Meylannie, Irene
PT. Dirgantara Indonesia (PT DI) is the first and only producer of airplanes in Southeast Asia. Since 2019, PT DI has recorded a high amount of demand for NC212i planes, which is nearly up to 6 units per year. Based on the company's current resources, PT DI only has the ability to meet the demand of 4 units per year. The company's production director, has realized that the biggest issue came from the lack of efficiency the current assembly processes. The Assembly line balancing concept that hasn't been applied to the company's final assembly process has resulted in a lot of unstructured implementation in the allocation of operations & operator tasks. This research aims to define the right operator assignment model for final assembly NC212i planes, so that cycle times are achieved with high operator utilization. The solutions to the problem in this research will be determined using a mixed integer linear programming model, processed by using two methods, which is the analytical and heuristic methods. The analytical method will be processed using the CPLEX Optimization software, while the heuristic method is developed from a mathematical model and converted into the form that more systematic stage of work. In the mathematical model, the function's main objective is to minimize the operator's idle time, considering that current work assignment procedures are still done based on the supervisor's subjectivity factor. Analytical and heuristic methods are developed from the same mathematical model, so both of them have the same objective function. The computational process in this research resulted in some solutions about operator assignment to reduced cycle times in accordance with target demand fulfilling, and reduced number of operators based on the operational needs. With these new job assignments, operator's idle time may be reduced and the average operator utilization increased from 36,68% to 78%.